Challenges in Sustaining the Seal of Good Local Governance: The Case of City of Carmona, Cavite - Sales, Eunice A.; Guevara- Canlas, Michelle; Garcia, Fil Vincent B.; Cid, Maria Charisma A.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2026)
This study focuses on the City of Carmona, Cavite, and aims to describe the problems the city has in maintaining the Seal of Good Local Governance. It seeks to determine what the challenges are to the Local Government Units’ (LGU) ability to keep the SGLG status, how these challenges affect the city’s operations, then provide recommendations to address these challenges. Based on the data and a